15. SURVEY OF KNOWLEDGE AND ATTITUDE ON STANDARD PRECAUTIONS OF HEALTHCARE WORKERS AT THU DUC CITY HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: To assess the knowledge and correct attitude towards standard precautions among healthcare workers (HCWs) at Thu Duc City Hospital and related factors in 2024.Subjects and Methods: A cross-sectional descriptive study was conducted on 618 HCWs at Thu Duc City Hospital.Results: The proportion of knowledge was 62%.Particularly, the highest figure of knowledge was related to safe injection practices and prevention of sharps injuries 92,4%, the lowest is basic knowledge of standard prevention 22.2%. In addition, the proportion of attitude was 77%. In particular, the attitude that all healthcare workers necessarily participated in annual training on standard precautions was 95.9%, besides the attitude was related to the statement “It is not necessary to clean instruments before disinfection and sterilization," at 21.2%.Conclusion: The knowledge and attitude of HCWs towards standard precautions were at a moderate level. There was a significant correlation between knowledge and attitude (p
Keywords: standard precautions; healthcare workers